Factors Relating to Giving Formula Milk to Babies Aged 0-6 Months at Upt Puskesmas Kajuara in 2022: Faktor-Faktor Yang Berhubungan Pemberian Susu Formula Pada Bayi Usia 0-6 Bulan Di Upt Puskesmas Kajuara Tahun 2022 - Nur, Arfan; Annisa, Nurul (Sekolah Tinggi Ilmu Kesehatan Gunung Sari, 2023)
Formula milk is milk that is specifically formulated as a substitute for breast milk for infants up to 6 months of age. The purpose of this research is to determine the factors related to giving formula milk to infants 0-6 months at UPT Puskesmas Kajuara in 2022. The research used was descriptive analysis with a cross approach. sectional means that the measurement of variables is only done once at a time, and the results of the study were obtained using the results of the chi square test statistic, obtained p-value = 0.001 P <0.05, there is a relationship between education and formula feeding at UPT Puskesmas Kajuara with test results chi square test statistic obtained p-value = 0.004 P <0.05. It means that there is a relationship between the economy and the provision of formula milk at the UPT Puskesmas Kajuara, with the results of the chi square test statistic test obtained p-value = 0.002 P <0.05 Kata kunci : Knowledge, Education, Economy.